Examining the relationship between innovative product design, cognitive ergonomics, and the effectiveness of entity design-system: focusing on the environment of big data-driven interface - Shi, Jianhai; Md Yusoff, Irwan Syah; Yahaya, Mohd Faiz (IADITI ? International Association for Digital Transformation and Technological Innovation, 2024)
The evolution of design systems has undergone a transformative shift towards entity-based frameworks. These systems represent a paradigmatic departure from traditional design approaches by structuring design elements around modular, reusable components known as entities. This study examines the elements that affect entity-based design system effectiveness and its effects on computer-related sectors. The study examines how creative product design, cognitive ergonomics, and big data-driven interfaces affect system efficacy. The study also examines how information processing efficiency mediates and technology infrastructure moderates the relationship between design elements and system results. Data was collected from 254 Chinese design system specialists and practitioners using quantitative methods. Participants' design, technology, and system efficacy perceptions were assessed using a standardized questionnaire. AMOS was used for mediation and moderation analyses to evaluate study hypotheses and examine variable correlations. This study found strong correlations between design elements, technology capabilities, and entity-based design system efficacy. Innovative product design, cognitive ergonomics, and big data-driven interfaces had an impact on system results, both individually and together. Information processing efficiency was a key mediator, while technology infrastructure moderated system efficacy. This study adds to the literature by revealing the complex elements that affect entity-based design systems in computer-related sectors. The study improves our theoretical understanding of design systems by investigating the relationship between design factors, technology capabilities, and system results. It also offers practical advice for organizations looking to improve their design processes and user experiences.